The most common health care services needed by university students and employees - APAYDIN KAYA, MEMNUNE ÇİĞDEM; ÇİFÇİLİ, SALİHA SERAP (MARMARA UNIV, FAC MEDICINE, 2020)
Objectives: The identification of the health needs of university students and staff may be the first step in improving public health approaches. The aim of his study was to investigate the most needed health care services by the university students and employees. Materials and Methods: A cross-sectional study was carried out with 864 representative individuals on Marmara University Goztepe Campus, Istanbul, Turkey. All participants were given a questionnaire including questions about the sociodemographic characteristics and health status, healthy lifestyle behaviours and health needs. Results: The mean age of the participants was 24 +/- 7.9 years. The number of participants who had periodic health maintenance/check-up was 11.4%. Smoking and alcohol use prevalence was similar for students and employees (30.9% and 30.2%). Depression screening was found to be positive in 67.4% of the participants (58.7% of the employees, 69.7% of the students).The most commonly requested information was on healthy nutrition (42.4%), followed by screening for diseases (32.3%), emergency situations/first aid (31.2%), exercise counselling (28.6%) and prevention of chronic diseases (27.8%). Conclusion: Our findings show that the most needed health care services are psychological counselling, periodic health controls, health promotion counselling and first aid training.
Keywords: Prevention and control; Primary health care; Occupational health; Depression